Effect of irrigation levels and nutrient sources on growth and yield of wheat (Triticum aestivum L.) - Nand, Vishuddha; Singh, G.R.; Kumar, Rajesh; Raj, Som; Yadav, Brijesh (Annals of Agricultural Research, 2014)
The present investigation was conducted at Narendra Deva University of Agriculture &Technology, Narendra Nagar (Kumarganj), Faizabad (U.P), during winter 2008-09. The experiment was laid-out in split-plot design. The treatments consisted of four irrigation levels (I1-0.8 IW/CPE ratio, I2-1.0 IW/CPE ratio, I3-three irrigation at CRI, late jointing and milking stage and I4-five irrigations at CRI, maximum tillering, late jointing, flowering and milking stage) in main plot and four nutrient sources viz., F1- 100% NPK through chemical fertilizers (120: 60: :40 kg NPK ha-1), F2-75%NPK + 25% nitrogen through FYM, F3-75% NPK + 25% nitrogen through bio-compost and F4-75%NPK +Azotobactor in sub plots. Results revealed that the growth parameters, yield attributes and yield increased significantly due to various moisture regimes and nutrient sources. The growth parameters, like plant height, number of shoot (m-2), leaf area index, dry matter accumulation (g/m-2) were increased significantly under 5 irrigations with 100% NPK through chemical fertilizers (120:60:40, kg NPK ha-1). The maximum grain yield was recorded with 100% NPK through chemical fertilizer i.e. 46.3 q/ha which was 7.34, 12.52, and 21.5% higher over 75%NPK + 25% nitrogen through bio-compost, 75%NPK + 25% nitrogen through FYM and 75% + 25% NPK + Azotobactor, respectively. All the yield attributes were significantly higher in the same treatment than 0.8, IW/CPE ratio and 3 irrigations at critical stages and at par with 1.0, IW/CPE ratio. Maximum water use efficiency (207.68 kg ha-cm-1) was at 0.8 IW/CPE ratio along with 100% NPK through chemical fertilizers (120:60:40, kg NPK ha-1).The maximum cost of cultivation (25,550 Rs ha-1), gross income (58,950 Rs ha-1), net income (33,400 Rs ha-1) and benefit: cost ratio (1.30) was obtained under 5 irrigations at CRI, maximum tillering, late jointing , flowering and milking stage along with 100% NPK through chemical fertilizers (120:60:40 kg ha-1) followed by cost of cultivation (25,030 Rs ha- 1), gross income (57,650 Rs ha-1), net return (32,620 Rs ha-1) and benefit: cost ratio (1.30 ) under irrigation at 0.8 IW/CPE ratio along with 100% NPK through chemical fertilizers (120:60:40 ha-1).